A study of e-shopping intention in Malaysia: The influence of generation X & Y - Mansori, Shaheen; Cheng, Boon Liat; Lee, Hui Shan (AENSI, 2012)
Developments in the commercial sector, coupled with the increasing popularity of the Internet in recent years, have made Malaysian companies more aware of the importance of E-business ingaining a competitive edge in the global market. Therefore, a better understanding of the factors that influence online shopping intention would help in planning better marketing strategies in targeted segments. In this study, five variables on online shopping intention were selected, namely perceived benefits, website characteristics, perceived risks, perceived pricing as well as product and service attributes. Findings from 200 respondents of Generation X and Y showed that four factors significantly influenced online shopping intention. The one exception wasproduct and service attributes. The generation gap was found to have a moderating effect on the relationships between perceived benefit, website characteristics, and online shopping intention.